(untitled) (Medico Legal Update, 2021)
Background: Broken families It is the family under divorce, separation, death of father, death of mother and death of both parents. It is the legal termination of marriage. It is also the dissolution of marriage that is contracted between husband and wife by the judgment of a court of competent jurisdiction or by an act of the legislature. Separation and divorce have exclusion and negative effects on the behavior of children as well as the burden of education for those in charge of it, which involves risks to the psyche and the degree of coping with children. Objectives: To determine broken families among secondary school adolescents, assess secondary school’s adolescents’ behaviors, determine the impact of broken families on adolescents’ behaviors, and to findout the relationship between adolescent’s behaviors underbroken family and their socio-demographic characteristics of age, gender, parent’s education levels, family type and socio-economic status. Methodology: Anon-probability (purposive) sample of (555) students, whose age are between 12 to 18 years have been selected; the sampling of study is divided into two stages which include: First stage: the school’s selection by cluster, the AL-Najaf City divided to six districts, the schools selected randomly (36) school’s boys and girls, from (130) total schools .Second stage: students under broken family selection by using the purposive sampling, while control group from each school students were randomly selected. Results: Indicate that there is significant relationship between the adolescent’s gender under broken family and their behavior domain excessive suffering, poor anger control and poor social conformity. While there is a non-significant relationship between the adolescent’s gender under broken family and their other behavior domains. The results show that there is a highly significant relationship between adolescent’s Educational level under broken family and their behavior domain poor impulse control and poor anger control. While there is a non-significant relationship between the adolescent’s Educational level under broken family and their other behavior domains. Conclusion: That most of the secondary school’s adolescents under broken family have Behavior problems. Recommendation: To the Governments and Schools should create awareness on the ills of broken homes on the academic, emotional and social adjustments of students through training, workshops and seminars. Parents should be enlightened on the need to stay together as husband and wife to raise a good family